Effect of Structured Teaching Programs (STP) on Knowledge Regarding the Impact of Internet Addiction (IA) among Adolescents of Selected Nursing College, Mangalore - Jayaprakash CS; Pradeep M (RGUHS Journal of Nursing Sciences)
Background Continuous and easy access to the Internet provides tremendous opportunities for adolescents to socialize connect with their peers as well as complete strangers from across the world. The problem of Internet addiction has plagued several nations particularly India. The effects of Internet addiction include feelings of loneliness increased anger despair and anxiety. Aim To assess the effect of structured teaching program STP on knowledge regarding impact of Internet addiction IA among adolescents of a selected nursing college Mangaluru. Methodology One group pre-test post-test design was adopted for the study and a stratified random sampling method was used to select 60 nursing students. A structured knowledge questionnaire was used to assess the levels of knowledge on the impact of Internet addiction. Results The pre-test scores showed that 56 91.8 had poor knowledge and 4 6.6 had average knowledge. After the structured teaching program the post-test scores showed that 49 80.3 had good knowledge 10 16.4 had average knowledge and 1 1.6 had poor knowledge. Conclusion The study concludes that adolescents have Internet addiction issues and health education to adolescents about the psychosocial impact of Internet addiction would help to promote healthy habits towards usage of the Internet and social media.